Determination and static analysis of the chassis model for electric vehicles - ERHAN, KORAY (My University, 2023)
Vehicle technology with an internal combustion engine emerged at the end of the 19th century. Although it is not very well known, the first prototype studies of the electric vehicle coincide with the same period. Today, factors such as global warming, pollution and the decrease in fossil fuel reserves accelerate the transition to electric vehicle technology. In this context, a new system structure is needed for electrically driven systems differently from traditional vehicle structures. In this study, a chassis design for an electric vehicle is carried out. While designing, the part where the battery pack will be placed has been modeled and simulated with the help of the ANSYS program to protect the battery and electronic components that are particularly sensitive to impacts. In order to be successful in abuse tests such as Crush and Crash tests specified in the regulations and standards, the material selection and design should be done correctly. In this context, the right materials are determined as a result of the researches and 3D simulations are made and crash tests are carried out in the simulation environment. As a result, tube type chassis was chosen among many chassis models and 7079 aluminum alloy was found suitable as raw material. According to the simulation results, it is seen that the design and the selected alloy are suitable.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Engineering, Computing & Technology (ENG); Electric vehicle; Battery; Electric vehicle chassis; Chassis model; Electric vehicle static analysis; Static analysis; Crash and crush.